IMPACT OF THE COMPUTER ON HUMAN LIFE AND HEALTH (Scientific journal of the Fergana State University, 2024)
What does computer mean in our life? Can we, today's youth, work without computers? In a short time, the computer has become an indispensable part in many areas of human life: it is already indispensable at work, it is difficult to imagine learning without it, and, of course, it is one of the most favorite pastimes for children. Search for information, relax, communicate, etc.